Tripterygium wilfordii Hook F combination therapy with methotrexate for rheumatoid arthritis: An updated meta-analysis. (10th May 2023) - Luo, Yijun; Hou, Xiaoxiao; Xi, Anran; Luo, Mengxian; Wang, Keer; Xu, Zhenghao
Abstract: Ethnopharmacological relevance: Rheumatoid arthritis (RA) is a chronic, systemic inflammatory arthropathy. Tripterygium wilfordii Hook F (TwHF) is common herbal medicine for the treatment of RA in China. However, many important issues, such as efficacy, safety and optimal doses of the combination therapy of TwHF and Methotrexate (MTX) for RA remain to be evaluated. Aims of the study: This study aims to evaluate the efficacy and safety of combination therapy of TwHF and MTX for RA by meta-analysis of randomized clinical trials (RCTs). Material and methods: Relevant literature was searched from English (PubMed, Web of Science, EMBASE, and Cochrane library) and Chinese databases (WanFang, VIP, CNKI) until December 2021. Response rates and rates of adverse events (AEs) were independently extracted and analyzed. Results: Fourteen randomized controlled trials (RCTs) were included with a total of 1446 patients, which included eight new RCTs with a total of 803 new patients when compared with the previous meta-analysis (Wang et al., 2017). Compared to MTX monotherapy, TwHF + MTX was revealed a higher effective rate (RR = 1.15, 95% CI: 1.10, 1.21), partial remission rate (RR = 1.27, 95% CI: 1.15, 1.40) and remission rate (RR = 1.31, 95% CI: 1.11, 1.55). The addition of TwHF benefited the clinical symptoms (such as tender joint count) and most laboratory indexes (such as the tumor necrosis factor-α). According to the subgroup analyses, the efficacy of the TwHF + MTX seems to be positively associated with the dose of TwHF (10 mg/d vs 30–60 mg/d), negatively related to the dose of MTX (∼10 mg/w vs ∼15 mg/w) and methodological risk of bias of included RCTs, and unrelated to the duration of therapy (12-week vs 24-week). For safety, the addition of TwHF did not increase the risk of most AEs and even reduced the risk of infection and liver AEs. Conclusion: Combining TwHF with MTX may be a superior strategy in the treatment of RA compared with MTX monotherapy. The optimal combination of TwHF + MTX therapy might be TwHF at 30–60 mg/d with MTX (∼10 mg/w). Further high-quality double-blind RCTs may be able to change the conclusions of our study, which are still warranted. Graphical abstract: Image 1 Highlights: Fourteen RCTs involving 1446 patients were included in this meta-analysis. TwHF + MTX revealed a higher effective rate in RA treatment compared with MTX alone. The addition of TwHF is well toleranted and may reduce the risk of specific AEs. The optimal strategy may be TwHF at 30–60 mg/d, MTX at ∼10 mg/w, and for 12 weeks.